INVESTIGATION OF THE EFFECTS OF BANDITRY ON EXTENSION SERVICES DELIVERY AND CROP PRODUCTION ACTIVITIES IN ZAMFARA STATE NORTH-WEST, NIGERIA - Ekpa, Daniel; Adeola, Segun S.; Ojoko, Emmauel A.; Amadu, Altine (FUDMA JOURNAL OF SCIENCES, 2025)
The study analyzed the effects of banditry on extension services delivery and crop production activities in Zamfara State North-West, Nigeria. A total of 261 crop farmers and 33 extension workers were sampled using multi-stage sampling techniques. The study used primary data which was collected using a structured questionnaire. Analytical tools such as descriptive statistics, Binary Logit regression model, and paired t-test were used in achieving the stated objectives. The results of the socio-economic characteristics revealed that the mean age for farmers and extension workers were 49 and 47 years old respectively. The result on the effect of banditry on extension delivery services showed that variables such as Frequency of banditry attacks, availability of security personnel, distance to extension delivery service areas, and blocking of local routes by bandits were all statistically significant, thus shows negative effect on extension delivery services to rural farmers. The analysis on the effect of banditry on crop income obtained by the farmers showed that before the onset of banditry, the farmers were realizing an average crop income of 302,398.99/ha, but as the bandits continued to invade their communities, the crop income now drastically dropped to 128,587.69/ha with a negative difference of -173,811.3 (284.65kg). It was recommended that government should improve the condition of service of the extension agents through regular recruiting more staffs, full armed security escorts and special allowances. These would facilitate effective extension delivery services to the rural farmers.
Keywords: Extension Services; Crop Farmers; Banditry Effect; Income